UNCERTAINTY QUANTIFICATION USING THERMOCOUPLE AND ARDUINO® COMPATIBLE HARDWARE - da Silva, L. R. R.; Ferreira-Oliveira, J. R. (Revista de Engenharia Térmica, 2021)
Temperature is a critical aspect in the control of processes in engineering. The measurement, however, must take into account not only the accuracy of the sensor but also the implementation costs and uncertainty. Thermocouples are one of the most widely used temperature measurement methods combining low costs, high measurement ranges, and relatively good accuracy. The acquisition system, however, is usually expensive. This paper evaluated the uncertainty in the temperature measurements of a K-type thermocouple using low cost Arduino® compatible hardware as a data acquisition system. This set was calibrated using a thermostatic distilled water bath at both freezing and boiling phase change points. The equations for uncertainty calculation were fully developed, and the procedures described serve as a reference for uncertainty assessment for thermocouples with other data acquisition systems. Although the calibration was the most significant contributor, the low variability of measurements shows the system has good stability and is a fine choice for industrial applications. The calculations are easy to implement as a routine for several measurements and guarantee results up to the international reference standard.